2016
DOI: 10.1146/annurev-micro-102215-095557
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Evasion and Endoplasmic Reticulum Subversion: The Yin and Yang ofLegionellaIntracellular Infection

Abstract: The gram-negative bacterial pathogen Legionella pneumophila creates a novel organelle inside of eukaryotic host cells that supports intracellular replication. The L. pneumophila-containing vacuole evades fusion with lysosomes and interacts intimately with the host endoplasmic reticulum (ER). Although the natural hosts for L. pneumophila are free-living protozoa that reside in freshwater environments, the mechanisms that enable this pathogen to replicate intracellularly also function when mammalian macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 148 publications
1
89
0
1
Order By: Relevance
“…Legionella is able to replicate intracellularlly in macrophages that have phagocytized aerosolized bacteria, and several studies have shown that Legionella pneumophila creates endoplasmic reticulum (ER)-like vacuoles that support intracellular replication. Through this mechanism the bacteria are able to interfere host autophagy processes, which is an ancient cell autonomous defense pathway based on ER-derived membranes to target intracellular pathogens for destruction [5558]. The presence of Legionella in our BB samples could be explained by this mechanism, but future studies focused on the chronic presence of these bacteria in the respiratory system will be needed to confirm these findings and their medical implications.…”
Section: Discussionmentioning
confidence: 87%
“…Legionella is able to replicate intracellularlly in macrophages that have phagocytized aerosolized bacteria, and several studies have shown that Legionella pneumophila creates endoplasmic reticulum (ER)-like vacuoles that support intracellular replication. Through this mechanism the bacteria are able to interfere host autophagy processes, which is an ancient cell autonomous defense pathway based on ER-derived membranes to target intracellular pathogens for destruction [5558]. The presence of Legionella in our BB samples could be explained by this mechanism, but future studies focused on the chronic presence of these bacteria in the respiratory system will be needed to confirm these findings and their medical implications.…”
Section: Discussionmentioning
confidence: 87%
“…One potential MTOR-independent LCV expansion mechanism could be a direct membrane acquisition from other intracellular compartments. Indeed, early secretory vesicles tether and directly fuse with the LCV [6,68] thus it was tested whether the secretory compartment contributes to LCV expansion during MTOR suppression. To this end, Myd88-/- BMMs infected with Δ flaA bacteria were treated for 3hrs with PP242 and brefeldin A to disperse the Golgi compartment or nocodazole to block microtubules-dependent vasicular trafficking during the late LCV expansion phase (Fig 8i).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that Legionella spp., typically have large substrate repertoires, although the effector set can be quite distinct from species to species (Gomez-Valero, submitted). The functions of effectors that have been revealed up to now target many cellular pathways and different eukaryotic organelles, including cell uptake and exit, endocytosis, vesicle trafficking, autophagy, mitochondria, cytoskeleton, ubiquitination/proteasome, ribosome, transcription factors, and the nucleus (Escoll et al 2016; Finsel and Hilbi 2015; Qiu and Luo 2017; Sherwood and Roy 2016). (see Chapter “ Subversion of Host Membrane Dynamics by the Legionella Dot/Icm Type IV Secretion System ”).…”
Section: Comparisons Of Effectors Secreted Through Different Dot/imentioning
confidence: 99%